Further examination of DSM‐5 antisocial personality disorder and psychopathy: Findings from a female correctional sample. (30th July 2020) - Wygant, Dustin B.; Engle, John E.; Sellbom, Martin
Abstract: A longstanding concern regarding the Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnosis of antisocial personality disorder (ASPD) has been its poor coverage of the construct of psychopathy. The most recent edition, the DSM‐5, has proposed an alternative model of personality disorders (AMPD) in Section III of the manual to rectify some of these concerns by offering a trait‐based model comprised of seven personality traits and a psychopathy specifier containing three additional traits. The current study sought to replicate and expand on previous findings that the AMPD operationalization of ASPD was more closely aligned with various measures of psychopathy than the traditional DSM‐5 Section II ASPD diagnosis. The current study examined 200 incarcerated female offenders, who completed a measure of the AMPD, traditional ASPD and two models of psychopathy. Analysis showed that Section III ASPD outperformed Section II ASPD in predicting scores on various measures of psychopathy. These findings are consistent with the previous findings that did not examine incarcerated female offenders and suggest that the AMPD operationalization of ASPD is more aligned with psychopathy than its Section II counterpart. © 2020 John Wiley & Sons, Ltd.